Carbamazepine-Induced Stevens-Johnson Syndrome and HLA-B*1502 Screening among First-degree Relatives of Index Patients - Siqing Ee; Siew-Kiang Tan; Yong-Kwang Tay (Wolters Kluwer Medknow Publications, 2019)
Background: Carbamazepine (CBZ) is often implicated in drug-induced Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN). CBZ-induced SJS/TEN is strongly associated with the HLA-B*1502 allele in Southeast Asia. Objectives: The objective was to determine the prevalence of HLA-B*1502 allele in patients with CBZ-induced SJS/TEN and in their first-degree relatives. Materials and Methods: Ten cases of CBZ-induced SJS/TEN from a single center were contacted and offered HLA-B*1502 genotyping for themselves and their first-degree relatives. Eight patients and 12 relatives consented for genotyping. Results: HLA-B *1502 was positive in all patients who were tested, of whom 50% of them were Malay and 50% were Chinese. The frequency of the HLA-B*1502 allele in the first-degree relatives was 58%. Conclusion: HLA-B*1502 is common in first-degree relatives of patients with CBZ-induced SJS/TEN.